The Analisis Sosiologi Sastra Dalam Film Yuni Karya Kamila Andini: Analisis Sosiologi Sastra Dalam Film Yuni Karya Kamila Andini - Nadila Angelina (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research discusses the sociology of literature in literary works, namely the film Yuni by Kamila Andini. The purpose of this study is to describe aspects of literary sociology in the form of social problems in the film Yuni by Kamila Andini. The method used in this research is descriptive qualitative. The data in this research is in the form of dialog conversations contained in the film Yuni by Kamila Andini. Data collection techniques used to obtain research data are listening and note-taking techniques. The data analysis technique used is content analysis technique in the form of reviewing, observing, interpreting the contents of the film Yuni by Kamila Andini. The result of this study is that there are aspects of literary sociology in the form of social problems 1) poverty, 2) crime, 3) family disorganization, 4) problems of the younger generation, 5) violation of community norms, 6) bureaucracy.